2012
DOI: 10.1159/000340016
|View full text |Cite
|
Sign up to set email alerts
|

The Clinical Meaning of Intramammary Lymph Nodes

Abstract: Objective: The clinical meaning of intramammary lymph nodes (iMLNs) is uncertain. We wanted to describe the clinical characteristics and understand the implications of iMLNs detected by sentinel LN biopsy (SLNB). Methods: We reviewed the clinical, radiological and pathological records of women diagnosed with invasive carcinoma of the breast at the Samsung Medical Center between January 2001 and January 2011. A total of 69 patients were identified, and SLNB was performed in 31 patients. Results: Of the 69 patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…They are involved in a variety of clinical situations, including benign lesions, tumor metastases, breast lymphomas and breast cancer, where their importance is not fully established. Nevertheless, there is evidence that IMLNs are an independent factor for poor prognosis, and they may change therapeutic decisions [3] . Patients with metastatic IMLNs had more aggressive cancers with lymphatic and vascular invasion as well as increased axillary lymph node metastases [4] .…”
Section: Discussionmentioning
confidence: 99%
“…They are involved in a variety of clinical situations, including benign lesions, tumor metastases, breast lymphomas and breast cancer, where their importance is not fully established. Nevertheless, there is evidence that IMLNs are an independent factor for poor prognosis, and they may change therapeutic decisions [3] . Patients with metastatic IMLNs had more aggressive cancers with lymphatic and vascular invasion as well as increased axillary lymph node metastases [4] .…”
Section: Discussionmentioning
confidence: 99%
“…Their role in lymphatic drainage of breast regions is important, although it is not known if they represent true sentinel nodes or if lymphatic drainage to them comes from ectopic, independently developed pathways. Their incidence in various studies ranges between 0.7% and 48% [ 6 7 ] and can be found in all breast quadrants. IMLNs are involved in a variety of clinical situations, including benign situations, tumor metastases, breast lymphomas, and breast cancer, where their importance is not fully established.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, there is evidence that IMLNs are an independent factor for poor prognosis, and they may change therapeutic decisions. Patients with metastatic IMSLNs had more aggressive cancers with lymphatic and vascular invasion as well as increased axillary lymph node metastases [ 6 ]. The use of axillary SLN biopsy accurately represents the disease status of the axilla in cases of positive IMSLN, and the use of nomograms demonstrated that the risk of axillary metastasis was less than 10% [ 1 ].…”
Section: Discussionmentioning
confidence: 99%
“…Other in ammatory conditions such as tuberculosis have also been reported. [1] Although IMLNs can be located in any part of the breast, they are most commonly found in the upper outer quadrant. The prevalence of IMLNs has been reported to range between 1% and 28% [2 ].…”
Section: Imlns Have Received Little Attention Compared To Axlns As Pomentioning
confidence: 99%